2020
DOI: 10.3389/fsoc.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Asylum Policy in a Divided Europe: Diverging Contexts, Diverging Attitudes?

Abstract: The large inflow of asylum-seekers in recent years has heralded a diversification in adopted asylum policies across European societies. Although a growing body of research has addressed these versatile approaches and their implications for the European integration project, insight into the social basis of these restrictive or open asylum policies remains underdeveloped. Hence, the current study provides detailed insight into public preferences for asylum policies and offers a new understanding of how these att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 70 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…The findings presented here are particularly relevant to new refugee receiving countries faced with massive displacement situations, but they, also hold pertinence to traditional refugee receiving countries. Recent evidence from 20 European countries shows that the policy, economic, and migratory context is not adequate to explain the cross-national divergences in attitudes toward asylum policy (van Hootegem et al, 2020). This study suggests that social cohesion indicators can serve as an alternative explanation to predict divisions in asylum policy across European countries.…”
Section: Discussionmentioning
confidence: 73%
“…The findings presented here are particularly relevant to new refugee receiving countries faced with massive displacement situations, but they, also hold pertinence to traditional refugee receiving countries. Recent evidence from 20 European countries shows that the policy, economic, and migratory context is not adequate to explain the cross-national divergences in attitudes toward asylum policy (van Hootegem et al, 2020). This study suggests that social cohesion indicators can serve as an alternative explanation to predict divisions in asylum policy across European countries.…”
Section: Discussionmentioning
confidence: 73%
“…Although there is some evidence from studies applying the vulnerability perspective that individuals with low SES report greater fears than those with a high SES (Sloan et al, 2020), others found a weak to no relation. However, group threat theory has a strong foundation in explaining outgroup attitudes through individual economic or status indicators, with those with high SES (often operationalized as either the (perceived) financial situation or educational attainment) experience lower realistic and symbolic threat from outgroups, resulting in more positive attitudes (Jacobs et al, 2019;Marfouk, 2019;Van Hootegem et al, 2020). With this in mind, we expect the following: H6: Lower educated individuals report greater fear of terrorism than higher educated individuals.…”
Section: The Current Studymentioning
confidence: 99%
“…Many studies of outgroup attitudes and prejudice have shown that both individual (age, gender, socioeconomic status (SES), etc.) and contextual factors, like economic conditions and outgroup size, provide complementary insights into attitudes toward outgroups (Heizmann & Ziller, 2020; Hjerm, 2009; Lubbers et al, 2006; Sarrasin et al, 2012; Schlueter & Davidov, 2013; Van Hootegem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 To solve this issue while determining the relationship between the proposed factors, multilevel structural equation modeling (MSEM) is the best choice. 22 Currently, MSEM has been used in the fields of public health policy [23][24][25] and adolescent health, 26,27 but rarely in health technology use.…”
Section: Introductionmentioning
confidence: 99%